2019
DOI: 10.1039/c9tc02391g
|View full text |Cite
|
Sign up to set email alerts
|

Microwave synthesis of MoS2/MoO2@CNT nanocomposites with excellent cycling stability for supercapacitor electrodes

Abstract: Herein, we present an ultrafast microwave approach for fabricating MoS2/MoO2@CNT nanocomposites toward supercapacitor electrodes with excellent cycle stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 73 publications
1
44
1
1
Order By: Relevance
“…As shown in Fig. 7c, the GCD curves of Ni 2 P//AC cell at different voltages were also between 1.2 and 1.6 v. The galvanostatic charging and discharging processes take the same time, which indicated that the device had strong electrochemical reversibility [42]. respectively.…”
Section: Electrochemical Characterization For the Assembled Ascsmentioning
confidence: 81%
“…As shown in Fig. 7c, the GCD curves of Ni 2 P//AC cell at different voltages were also between 1.2 and 1.6 v. The galvanostatic charging and discharging processes take the same time, which indicated that the device had strong electrochemical reversibility [42]. respectively.…”
Section: Electrochemical Characterization For the Assembled Ascsmentioning
confidence: 81%
“…Both symmetric and asymmetric supercapacitators were formed, it was observed that the CNT layer provides a good transport path for the electrolytic ions; as a result, the capacitance was enhanced by 187.1%, as compared with bare CNTs after 25 000 cycles at a current density of 5 A g −1 . The optimized capacitance observed is 228.4 F g −1 at 0.5 A g −1 with a maximum energy density of 11.88 W h kg −1 and power density of 2 kW kg −1 . Tiny MoO 3 nanocrystals were grown on 3D MoS 2 frameworks by the hydrothermal route, it is observed that the chemical binding here is by oxygen bonding.…”
Section: Applications Of Mos2 For Energy Conversion and Storagementioning
confidence: 97%
“…[106][107][108] Similar chemical doping (e.g., B, P, S, and F) was also investigated to enhance the power performance via improving the surface pseudocapacitance [109] and quantum capacitance, [110] regulating interface compatibility, [109] enlarging potential window and so on. [111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] Like in the case of graphene, chemical doping of other 2D materials can also regulate the energy storage performance.…”
Section: Chemical Doping and Functionalizationmentioning
confidence: 99%
“…There are several ways that chemical doping could offer to contribute to the improvement in energy storage performance, including the pseudocapacitance (with new redox active center), boosted charge mobility and DOS at the Fermi level (e.g., charge charrier density, the C q in Equations (2) and (3), a new gap to give quantum capacitance ( C tot increased, Equation (2)), the increased interlayer spacing to improve ion accessibility and C dielec ( C tot increased, Equation (2)), the enhanced stability, and the newly formed charge injection to improve binding ability with ions (reducing the d in Equation (1)). [ 101–126 ] A quick instance is O functional groups on graphene's surface, which offer additional pseudocapacitance. Nevertheless, these O‐functionalized groups are generally unstable, reducing the charge mobility of graphene.…”
Section: Engineering 2d Materials For Supercapacitor Applicationsmentioning
confidence: 99%